What Is the Mediating Role of Communication Skills and Sexual Satisfaction between Job and Life Satisfaction of Healthcare Employees? - Sema Üstgörül; Catalin Popescu (Behavioral Sciences, 2023)
There are three areas of harmony in human life that are related to each other: “work environment”, “love-to be loved-sexual area” and “social environment”. Incompatibility and dissatisfaction in one area can also affect other areas. Therefore, the aim of this study is to examine the relationship between job satisfaction, life satisfaction, communication, and sexual satisfaction of healthcare employees. The data collected by questionnaires from 394 employees working in university hospitals in Turkey were analysed using SPSS and AMOS programs. The findings show that there is a positive relationship between the job and life satisfaction of employees of healthcare organizations. Additionally, the findings revealed that communication skills and sexual satisfaction have a mediating role between job satisfaction and life satisfaction of employees in healthcare organizations. Life satisfaction, sexual satisfaction, and relationships are some of the factors that should be considered by healthcare organizations. It would be beneficial to employees and the public if health policy makers implemented programmes to enhance job satisfaction.